Influenza Polymerase Inhibitors: Mechanisms of Action and Resistance - Takashita, Emi (Cold Spring Harbor perspectives in medicine, 2021)
The influenza virus RNA-dependent RNA polymerase is highly conserved among influenza A, B, C, and D viruses. It comprises three subunits: polymerase basic protein 1 (PB1), polymerase basic protein 2 (PB2), and polymerase acidic protein (PA) in influenza A and B viruses or polymerase 3 protein (P3) in influenza C and D viruses. Because this polymerase is essential for influenza virus replication, it has been considered as a target for antiviral agents. Recently, several polymerase inhibitors that target each subunit have been developed. This review discusses the mechanism of action, antiviral activity, and emergence of resistance to three inhibitors approved for the treatment of influenza or in late-phase clinical trials: the PB1 inhibitor favipiravir, the PB2 inhibitor pimodivir, and the PA inhibitor baloxavir marboxil.